Co-expression of FVIII with human IGG FC Fragment or mouse IL-10 in encapsulated G8 myoblast cells as a potential treatment of hemophilia A - Kanketayeva, Zhansaya (Nazarbayev University School of Science and Technology, 2016)
In this master thesis study we have shown that recombination G8 myoblasts, encapsulated in alginate-PLL microcapsules can successfully secrete detectable levels of both Fc and IL-10 out of the capsules and sustain good viability, showing the potential of co-delivering FVIII by encapsulated cells.
Keywords: FVIII; G8; IL-10; Fc